Legal Protection Of Occupational Safety And Health In The Employment Agreement - Yunus, Muhammad (Legalpreneur Journal, 2022)
PT. Indo Hutama Jaya, which is engaged in Civil Mechanical Construction, has been registered with the supervision of the Ministry of manpower, there are some irregularities or problems, namely the right to guarantee Occupational Safety and health for workers who work at PT. Indo Hutama Jaya, such as incomplete use of PPE that has been provided by the company or does not follow the work procedures set by the company. To prevent or minimize the occurrence of accidents and occupational diseases, the PT. Indo Hutama Jaya implement SMK3. The research method used is normative and empirical juridical research. The nature of the research used in this study is descriptive analysis. The data sources used in this study are primary and secondary data. The method of data analysis used in this study is descriptive qualitative. Based on the results of the study, the conclusion in this study is a work Agreement set forth in Article 1601 A of the Civil Code must contain the terms of the validity of the agreement in accordance with Article 1320 of the Civil Code such as the agreement of both parties, the existence of skills in making alliances, the existence of a certain thing, and the existence of a lawful cause. Implementation of legal protection in PT. Indo Hutama Jaya is the legal protection of working hours and breaks, salaries or wages, bonuses or benefits, and the existence of facilities regarding Occupational Safety and health, such as personal protective equipment, guard posts, bathrooms. But in the employment agreement PT. Indo Hutama Jaya, workers do not receive protection regarding Occupational Safety and Health and workers are not included in the BPJS Ketenagakerjaan program. For the implementation of Occupational Safety and Health Protection at PT. Indus Hutama Jaya in accordance with law No. 1 Of 1970 On Occupational Safety. Legal protection of Occupational Safety and Health in the legislation in accordance with Law No. 1 of 1970 on Occupational Safety, especially Article 3 which stipulates the terms of Occupational Safety in the company. And Law No. 13 of 2003 on Labor that provides legal protection against labor/workers, wages, and welfare. The legislation that regulates Occupational Safety and health is also supported by government regulations, ministerial regulations, ministerial decisions on Occupational Safety and health (K3), ministerial instructions, and circulars and decisions of the Director General of Industrial Relations and Labor supervision.